Occupational Depression, Cognitive Performance, and Task Appreciation: A Study Based on Raven’s Advanced Progressive Matrices - Bianchi, Renzo; Schonfeld, Irvin Sam (Frontiers in Psychology, 2021)
The Occupational Depression Inventory (ODI) was recently developed to assess depressive symptoms that individuals specifically attribute to their work. Research on the criterion validity of the instrument is still in its infancy. In this study, we examined whether the ODI predicted performance on, and appreciation of, a cognitively challenging test. In light of the link established between clinical depression and neuropsychological impairment, and considering that individuals with depressive symptoms are more likely to feel helpless under challenging circumstances, we hypothesized that occupational depression would be associated with poorer cognitive performance and a darkened appreciation of the task undertaken. We relied on a sample of 1,359 educational staff members. We used an abridged version of Raven’s Advanced Progressive Matrices (RAPMs) as a cognitively challenging task and measure of cognitive performance. RAPMs assess so-called eductive ability (meaning-making and problem-solving abilities) through items of various degrees of difficulty. Transient mood was assessed with a three-item measure before RAPMs were administered. Task appreciation was assessed with a single-item measure after the completion of RAPMs. We found occupational depression to be negatively linked to cognitive performance. A two-step cluster analysis, in which ODI and RAPMs scores were used as classifiers, revealed two profiles of respondents. The first profile was characterized by relatively low levels of depressive symptoms and high levels of cognitive performance; the second profile, by relatively high levels of depressive symptoms and low levels of cognitive performance. The two profiles differed strongly from one another, as indexed by Cohen’s ds of 2.492 regarding depressive symptoms and 1.263 regarding cognitive performance. As anticipated, occupational depression predicted a darkened appreciation of the test. The association remained statistically significant, and largely unchanged, controlling for pretest mood and test performance. The highest levels of depressive symptoms were observed among individuals evaluating the task as “frustrating” and “discouraging.” Our study suggests that occupational depression predicts poorer cognitive performance and a negativized experience of cognitive challenge. Such features may be part of a self-sustaining loop fostering the maintenance of depressive symptoms. Future studies should examine the ODI’s criterion validity vis-à-vis job performance.